The Role of the Government Regarding Land Rights of Residents Affected by Abrasion - Ahmad Hadzikil Fahimi (JUSTISI, 2025)
This study aims to see that from the abrasion disaster, many residents have lost their land rights. In this case, the government must protect the rights of residents affected by the abrasion disaster. The research method used is an empirical juridical approach to the method of legislation. Novelty of the research is that the loss of land rights of residents affected by abrasion can be done through land registration so that their land rights can be protected by the government. Land registration is carried out to protect the rights of citizens with land registration the government can follow up the process of protecting land rights. The result of the research the government has tried to protect their rights by providing aid funds to its citizens, but there has been no announcement for citizens in the registration of land affected by abrasion. Conclusion in Land Regulation No. 24 of 1997, the legal status is considered invalid because it is not in line with the physical data or legal data that is used as strong evidence and the Jembrana Regency Government has made efforts to prevent the occurrence of abrasion disasters by banning beach sand mining and the manufacture of concrete to break sea waves.